Kritik atas Pemaknaan Hadis tentang Dayyūth di Media Sosial - Kholila Mukaromah (JIA (Jurnal Ilmu Agama), 2023)
This paper aims to criticize the meaning of the hadith which talks about dayyūth which is spread on social media in the perspective of qira’ah mubādalah. This study is included in the library research where the data is analyzed using qira’ah mubādalah analysis. The study begins with searching for some hadīths that contain the term dayyūth. The results of the study show that: first, the hadith regarding dayyūth is found in a number of hadith books: Sunan al-Nasa’i no. 2512; Musnad Ahmad no. 5904, 5839, and 5117; Musnad Abī Ya’lā no. 5430, al-Mustadrak ‘ala Ṣahihayn li al-Ḥākim no. 226; Muṣannaf Abī Razzāq no. 19.521; dan al-Mu’jam al-Awsaṭ li al-Ṭabranī with meaningful editorial and hadith quality still at the level of accepted hadith (ṣaḥīḥ). Second, in the original meaning, dayyūth is addressed to someone who has given up his family to commit an abomination. In the analysis of qira’ah mubādalah, dayyūth is not only aimed at men, but also includes women who allow their partners or family to do things that are prohibited by religion. The prohibition of becoming a dayyūth is basically a signal to always remind each other to amar ma'ruf nahi munkar in the smallest sphere of society, namely the family. Third, the results of this interpretation are therefore considered not to support the meaning of the hadith dayyūth which is spread on social media which tends to partially and literally place the blame on men as husbands or heads of families and at the same time prohibit women from appearing in public, even if it's just a photo.